Management Changes in Public Institutions: Impact on Software Development Teams - Lopes, Fabian de Oliveira; Gadelha, Bruno (Proceedings of Workshop on Social, Human and Economic Aspects of Software (WASHES), 2021)
IT management and governance in the public area differ from the private area due to the business object and the expected return. Added to this difference are elective and non-elective seasonal management changes, which can impact IT management processes at various levels of its structure. The goal of this research is to analyze the impact on software development teams caused by these changes as well as their influence on the services made available to their users, answering highly relevant questions such as why the changes occurred and the process in which they occur.